Integrated monitoring of chemicals and their effects on four sentinel species, Limanda limanda, Platichthys flesus, Nucella lapillus and Mytilus sp., in Seine Bay: A key step towards applying biological effects to monitoring. (March 2017) - Burgeot, Thierry; Akcha, Farida; Ménard, Dominique; Robinson, Craig; Loizeau, Véronique; Brach-Papa, Christophe; Martínez-Gòmez, Concepción; Le Goff, Jérémie; Budzinski, Hélène; Le Menach, Karine; Cachot, Jérome; Minier, Christophe; et al.
Abstract: The International workshop on Integrated Assessment of CONtaminants impacts on the North sea (ICON) provided a framework to validate the application of chemical and biological assessment thresholds (BACs and EACs) in the Seine Bay in France. Bioassays (oyster larval anomalies, Corophium arenarium toxicity assay and DR Calux) for sediment and biomarkers: ethoxyresorufin- O -deethylase (EROD) activity, acetylcholinesterase (AChE) activity, lysosomal membrane stability (LMS), DNA strand breaks using the Comet assay, DNA adducts, micronucleus (MN), PAH metabolites, imposex, intersex and fish external pathologies were analysed in four marine sentinel species ( Platichthys flesus, Limanda limanda, Mytilus sp. and Nucella lapilus ). Polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs) and heavy metals were analysed in biota and sediment. Results for sediment and four species in 2008–2009 made it possible to quantify the impact of contaminants using thresholds (Environmental Assessment Criteria/EAC2008 : 70% and EAC2009 : 60%) and effects (EAC2008 : 50% and EAC2009 : 40%) in the Seine estuary. The Seine estuary is ranked among Europe's most highly polluted sites. Highlights: Three bioassays for sediment and nine biomarkers were analysed in four sentinel species in the Seine Bay. Observed values for biological responses and contaminant concentrations were compared with BAC and EAC thresholds. This study validates BAC and EAC thresholds by demonstrating relationships on a local scale.